2016
DOI: 10.1177/1071100716659037
|View full text |Cite
|
Sign up to set email alerts
|

A Coding System for Reoperations Following Total Ankle Replacement and Ankle Arthrodesis

Abstract: Level III, retrospective comparative cohort study based on prospectively collected data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 10 publications
(12 reference statements)
1
36
0
Order By: Relevance
“…This study identified a 9% rate of nonrevision reoperation. In comparison to the rates of 12% to 20% seen in the early experience with some other systems 25,29 and for TAA in general, 18 these results are encouraging.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…This study identified a 9% rate of nonrevision reoperation. In comparison to the rates of 12% to 20% seen in the early experience with some other systems 25,29 and for TAA in general, 18 these results are encouraging.…”
Section: Discussionsupporting
confidence: 49%
“…Reoperation and revision data were collected prospectively using the COFAS Reoperations Coding System. 18 Standing ankle radiographs were obtained preoperatively and at 2 postoperative time points: early (less than 12 months) and late (greater than 24 months). Radiographs were reviewed by 2 independent observers utilizing previously published measurement techniques.…”
Section: Data Collectionmentioning
confidence: 99%
“…23,33 The impact of AEs on outcomes is clouded by inconsistent or unclear reporting of AEs and lack of direct linking of AE to consequences. 10,22,27,40 AEs are uncommon in orthopedics but increase costs and negatively impact outcomes. 7 Millstone et al identified the likelihood of under reporting AEs in orthopedic procedures when using administrative databases and instead identified AEs at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…37 A coding system specific to increasing severity of reoperation for ankle surgery has also been reported. 40 Others have concurred that there is utility in severity weighted AE reporting. 4…”
Section: Introductionmentioning
confidence: 99%
“…42 Surgical treatment has been shown to improve unemployment rates and be cost-effective on a societal level. 38 Ankle arthritis is increasingly recognized as a major source of morbidity, impacting younger adults in their most societally and monetarily productive years (age 55 for fusions and 63 for replacements 130 ). This cohort of 55year-olds likely have 10 more productive work years prior to retirement as compared to hip or knee arthritis patients who are already in their retirement years (65 in total hip arthroplasty and 66 in total knee arthroplasty 106 ).…”
Section: Introductionmentioning
confidence: 99%